VD_FINDINFO Décision / 2013 / 254 vom 20. März 2013 - VD Tribunal cantonal (2013)
DÉTENTION PRÉVENTIVE, RISQUE DE FUITE, PROPORTIONNALITÉ | 212 CPP (CH), 221 al. 1 let. a CPP (CH), 227 CPP (CH), 393 al. 1 let. c CPP (CH)